Korelasi Keputusan Pembelian : Kualitas Produk, Persepsi Harga dan Promosi UD. Anugera Jaya - Alfina Rahmawati; Mariyatul Qibliyah; Dewi Cantika Rahmawati; Nindya Kartika Kusmayati (Fakultas Ekonomi Universitas Yos Soedarso, 2024)
The theme of consumer behavior is always interesting to discuss. Consumer behavior also changes with developments and changing times. Examining the factors that influence the consumer decision-making process before purchasing a product is the most widely researched consumer behavior. Around 60 studies related to consumer decision making can be found between 1998 and 2009 (Djatmiko, T., & Pradana 2016). Product quality, price perception, and product promotion are positively correlated with each other with the consumer's decision to purchase the item, according to several previous quantitative studies in Indonesia on this decision making. This article does not aim to evaluate research results, but to review marketing management literature regarding the correlation of purchasing decisions with product quality, price perceptions, and promotions.